"Arruando" vejo rio, homens, pedra & cal : a des-re-patrimonialização do sítio histórico tombado de Penedo-AL - SIlva, Daniella Pereira de Souza (2016)
The patrimonialization understood as a processo of resignification of places has been created conflicts as consequence of its territorialization in preexisting territories, forcing a meeting between culture, habits, modes and lifestyles consolidated andu nique, and the competitive tourist market of cities heritage. This study intended to understand how the patrimonialization is institutionally processed and how its daily perceived by the people in the historic sites preserved considering their relationship with the patrimonialization agents and the cultural landscape. We chosed the county of Penedo, situated at the Baixo São Francisco region in the state of Alagoas, because its preserved in the federal, state and county level. As principal objective we sought to understand which mechanisms, processes, strategies and conflicts are in the basis of the patrimonialization process of the historical preserved county of Penedo-AL, explaining the complexity of relationships between the external and internal agents of patrimonialization and the people of that area, to make it viable. This research was developed using as methodological way the qualitative approach and tried to stick in three structural issues: the changes and continuities in the county of Penedo as contributory factors of the patrimonialization process in its various dimensions; the multiple perceptions of/in the heritage landscape and, the patrimonialization perceived as a des-re-territorialization process. Those reflections around these issues allowed to conclude that the processo of patrimonialization afects the perception of cultural landscape by the residente population such as by the entreprenuers and self-employed people that “use” the historic área; that as na institutional process still persists weaknesses in policies and management, in the case of Penedo, in the county, state and federal scales. Moreover, the commodification of places woth competitive intente in the tourism sector, leads them to a process of des-re-patrimonialization that follows performing un continuum based on the population immobility of the historic sites preserved because new meanings are being created and new functions are being established as a consequence of the recognition of heritage through standardization instead of experience.